Класифікація екосистем Черемського природного заповідника з використанням картографічного методу - Конiщук, В.В. (Український фітоценологічний збірник, 2005)
Представлена детальная классификация экосистем Черемского природного заповедника (Волынская обл.) c использованием картографического метода. На VI уровне разнообразие экосистем составляет 73 единицы. In this paper the classification of Cheremskiy Natural Reserve ecosystems (Volyn Region) with using a cartography method are present. The detailed classification of ecosystems is given. The diversity of ecosystems consists of 73 assotiations on VI level.